Penambahan Berbagai Sumber Beta Karoten Alami Dalam Pakan Terhadap Peningkatan Kecerahan Warna Ikan Koi (Cyprinus carpio) Issue of Various Sources of Natural Beta Carotene In Feed To Koi Fish (Cyprinus carpio) Color Brightness Enhancement - Evan Aspirata Hulu; Syammaun Usman; Nurmatias Nurmatias (AQUACOASTMARINE, 2015)
The potential for aquaculture in Indonesia has a very promising opportunity.The ornamental fish have a beauty value of its body shape, active movement and colordiversion. Koi (Cyprinus carpio) is one type of ornamental fish that can be cultered. Koifish which have beautiful and bright colors can be have a high value. Natural colormatters in feed is done to improve and maintain the color of ornamental fish. Materialsof beta carotene used were astaxanthin, carrot powder and spirulina. The purpose ofthis research is to determine the best effect of natural beta carotene issue to increasecolors brightness in koi fish and determine the treatment efficient or not. This researchused Completely Randomized Design (CRD) with four treatments: T (without givingcolor material), W (carrots), S (spirulina) and A (astaxanthin) each of dose 3% andthree repetition. Data were analyzed with ANOVA system. The result has shown thatissue 3% of astaxanthin produce the best color brightness at 0,97 point than the othertreatment. The result showed that the treatment of color materials issue in feed wasefficient (benefit) because of the efficiency values smaller than 1 (one).Keywords: Cyprinus carpio, koi fish, color, carotenoids